Hot and cold marine extreme events in the Mediterranean over the period 1982-2021 - Simon, Amelie; Plecha, Sandra M.; Russo, Ana; Teles-Machado, Ana; Donat, Markus G.; Auger, Pierre-Amael; Trigo, Ricardo M. (Frontiers in Marine Science, 2022)
Marine temperature extremes are anomalous ocean temperature events, often persisting over several weeks or longer, with potential impacts on physical and ecological processes that often encompass socio-economic implications. In recent years, a considerable effort has been directed at the development of metrics allowing an objective characterization of both marine heatwaves (MHWs) and marine cold spells (MCSs). However, the majority of these metrics do not consider explicitly the spatial extent of the events. Here, we rank and evaluate the relative importance of marine temperature extreme events thanks to a metric, called activity, that combines the number of events, duration, intensity and spatial extent. According to this definition, in the Mediterranean basin between 1982 and 2021, summer 2018 experienced slightly more MHW activity than summer 2003, documented as an exceptional extreme event. Besides, MHW activities were higher in the last two decades while winter MCS activities were higher in the 1980s-1990s. The highest MHW activities occurred preferentially in the western Mediterranean while the strongest MCS activities took place preferentially in the eastern Mediterranean. Moreover, the duration, mean intensity, and activity of the three strongest MHWs are twice as high as those of the three strongest MCSs. The long-term tendency of extreme events activity shows an accelerated increase for summer MHWs (about +150 °C.days.10⁶km² ) and a linear decrease for winter MCSs in the Mediterranean (about -60 °C.days.10⁶km²) over the last four decades.